Juliana L. Knoepfmacher papers - Knoepfmacher, Juliana L., 1899-1974.
Correspondence, memoranda, speeches, lectures, writings, notes, case files, minutes, agenda, biographical material, printed matter, and other papers documenting Knoepfmacher's work as a child therapist and her writings on the treatment of children. Documents her professional associations and work as a training supervisor with the Jewish Board of Guardians in New York, N.Y. Includes writings pertaining to a Montessori school she directed in Vienna, 1927-1937, and files from the Paul Federn Study Group.
Psychoanalyst, social worker, and educator. Known primarily as Lia Knoepfmacher.
Collection material in English, with German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Jewish Board of Guardians; Paul Federn Study Group; Child analysis; Child psychology; Montessori method of education -- Austria -- Vienna; Psychoanalysis; Psychoanalysis -- United States -- Societies, etc; Social work with children -- United States; Educators; Psychoanalysts; Social workers